Disciplinary strategies or reactive measures? an analysis of coach sanctions in elite Danish handball leagues - Gençoglu, C.; Gümüs, H. (International Journal of Sports Science & Coaching, 2025)
This study analyzed coach sanctions in elite Danish handball matches across seven seasons (2017-2024), focusing on differences by league, gender, match period, and situational context. A total of 2978 matches and 398,054 events were collected from official match analyses. Sanctions were categorized by type (yellow card, 2-min suspension, blue card) and compared using chi-square tests and Spearman correlations. A two-minute retrospective event analysis was performed to identify triggers preceding coach sanctions using a custom Python code. The results showed that sanctions were more frequent in the Men's League than in the Women's League and occurred predominantly in the second half of matches. Positive correlations between coach and player sanctions were consistently stronger in the Women's League than in the Men's League (variable across seasons). Significant events such as goals, saved shots, technical mistakes, and turnovers were commonly recorded immediately before the coach's sanctions. Findings indicate that coach sanctions serve regulatory and strategic functions, with gender differences suggesting divergent disciplinary and management styles. These results highlight the role of situational pressure in triggering coach sanctions and suggest that coaching strategies should consider managing disciplinary responses under competitive stress.